2017
DOI: 10.1016/j.foodqual.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Sweet and sour discrimination abilities of elderly people compared to those of young adults in apple purée

Abstract: The number of elderly people is growing in Europe. A decrease in gustatory capacities (detection, identification, discrimination) is associated with aging. In the literature, discrimination abilities have been studied mainly in aqueous model solutions, but less is known about sensitivity in real food matrices. Moreover, in foods, taste interactions can occur and modify perceptions (masking effect). This study aimed to compare the discrimination abilities of elderly people and younger adults when tasting apple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The data corroborate with a study conducted by Neumann et al [23], in which sensitivity to sweet, salty, sour, and bitter tastes was compared between adults and the elderly. Mingioni et al [28] showed that the elderly are able to identify differences between sweet and sour concentrations in products and that this ability is relatively stable with age. Other researchers say that the perception of umami increases, while the sour and bitter tastes decrease as the individual gets older [25], agreement with our search.…”
Section: Discussionmentioning
confidence: 99%
“…The data corroborate with a study conducted by Neumann et al [23], in which sensitivity to sweet, salty, sour, and bitter tastes was compared between adults and the elderly. Mingioni et al [28] showed that the elderly are able to identify differences between sweet and sour concentrations in products and that this ability is relatively stable with age. Other researchers say that the perception of umami increases, while the sour and bitter tastes decrease as the individual gets older [25], agreement with our search.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while most studies of the decline in olfactory sensitivity with aging have assessed orthonasal olfaction, it has been suggested that the findings do not necessarily provide a reliable prediction of retronasal experience, especially when dealing with complex foods [ 9 , 36 , 37 , 38 ]. Research looking specifically at the age-related loss in the sense of taste (gustation) has revealed a decline in sensation for the majority of basic taste qualities [ 39 , 40 , 41 ]. That said, there is also some older evidence to suggest that people’s sensitivity to specific individual taste qualities may also change differentially across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…What this means, in practice, is that while some elderly individuals may be functionally anosmic, others may retain a level of olfactory functioning that is not much different from their younger counterparts. Another point to stress here is that, if anything, the decline in chemosensory function in the elderly often appears to be more apparent when assessed with pure tastants/olfactory stimuli than when assessed with real food stimuli (e.g., see [ 40 , 41 ]). Here, it would certainly also be interesting to know more about whether or not orthonasal and retronasal olfactory abilities decline at the same rate in the elderly [ 9 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consumer choices are affected by the sensory qualities of products, especially their taste. (1,2) Recent studies have shown that sweetness and sourness are the most important taste factors of apples in terms of consumer preferences. Some studies showed that the prediction of apples' sweetness and sourness is inadequate because sweetness and sourness perceptions are influenced by the comprehensive bias of the human taste perception system towards multiple components.…”
Section: Introductionmentioning
confidence: 99%